Molecular Detection and Prevalence of Hepatozoon canis in Dogs from Punjab (Pakistan) and Hematological Profile of Infected Dogs - Qamar, Muhammad; Malik, Muhammad Irfan; Latif, Muhammad; ul Ain, Qurat; Aktas, Munir; Shaikh, Rehan Sadiq; Iqbal, Furhan (Mary Ann Liebert, Inc, 2017)
The intraleukocytic parasite, Hepatozoon canis, causes the sometimes fatal tick borne disease canine hepatozoonosis. In this study, dogs from Islamabad, Lahore, and Multan Districts of the Punjab region of Pakistan were surveyed to investigate the presence and prevalence of H. canis infection and to determine the effects of the parasite on hematological parameters. Blood samples were collected from 151 domestic dogs (149 pet, 2 stray) of both sexes and varying ages. Data on sex, age, tick infestation, and clinical factors (body temperature, mucous membrane status, and presence of hematuria and vomiting) were collected. Using PCR, 18 dogs (11.9%) were found positive for the presence of H. canis DNA. Partial sequences of the 18S rRNA gene shared 99-100% similarity with the corresponding H. canis isolates. This epidemiological survey revealed higher prevalence of H. canis in Islamabad (11/49, 22.4%) compared to Lahore (3/52, 5.8%) and Multan (4/50, 8%) in Pakistan. No investigated epidemiological or clinical factors were found to be associated with the presence of H. canis (p>0.05) in dogs. H. canis positive dogs exhibited higher minimum inhibitory dilution (p=0.04), mixed inclusion (p=0.008) and relative distribution width of red blood cells (p=0.02), and lower hematocrit (p=0.03) and mean hemoglobin content (p=0.03) than did dogs in which H. canis was not detected. We are recommending this PCR-based protocol to the veterinary practitioners for the detection and/or confirmation of H. canis in dogs suspected for hepatozoonosis to improve their health status.
Keywords: dog; hematology; Hepatozoon canis; PCR; phylogenetic analysis